(untitled) (Ethiopian Journal of Economics, 2026)
Climate-smart agriculture (CSA) practices are serving as a fundamental element for achieving sustainable agricultural development while maintaining food security against the challenges of climate change. So far, the adoption of these practices by smallholder farmers has remained low. Hence, this study used panel data from two waves of the Ethiopian Living Standards Measurement Survey (LSMS), conducted in 2018/19 and 2021/22, to explore the determinants of CSA adoption, particularly soil and water conservation, agronomic practices, and livelihood diversification among smallholder farmers in Ethiopia. The determinants that facilitate or hinder the adoption of these CSA practices were identified using a multivariate Probit model. The results indicated that adoption rates were patently low: only 17.5% for soil and water conservation, 7% for agronomic practices, and 31% for livelihood diversification. The study found that female-headed households were less likely to adopt soil and water conservation and agronomic practices but more likely to diversify livelihoods. Education, extension services, mobile ownership, and drought shocks consistently promoted adoption across practices. Larger landholdings positively influenced soil and water conservation and agronomic practices but discouraged livelihood diversification. In contrast, family size, livestock holdings, and slope exhibited varied effects across the three practices. Greater distance to markets constrained the adoption of agronomic practices, while agroecological conditions also played a role in shaping both agronomic practices and livelihood diversification strategies. The findings suggest that strengthening access to extension services, promoting education, and enhancing CSA information distribution are critical for enhancing CSA adoption. Policies should also address gender disparities by providing targeted support to female-headed households. Improving market access and tailoring interventions to specific agroecological contexts would further facilitate adoption. Integrating land management with livelihood support could help reconcile the trade-offs posed by land size, livestock holdings, and household composition in shaping CSA adoption.